Nursing care in pediatric patients with burns and effects due to separation of the family bond - Lidys Padrón Fernández; Arelys Rebeca Álvarez González; María Mercedes Cedeño Cedeño (Universidad de Alicante, 2019)
Introduction: Burns are one of the main health problems in children. It is considered a frequent, but preventable event, which leads to a hospital stay that is often prolonged and can cause effects on the child due to separation from the family bond. The nursing professional who is in charge of the child's care should focus on an integral care, taking into consideration the physical, biological and psychological spheres. Objective: To determine the nursing care in pediatric patients with burns, and the effects of separation from the family bond at "Baca Ortiz" Hospital in Quito, Ecuador. Method: Decriptive, quantitative, non-experimental. Research population: Out of a total of 72 nursing professionals, 40 nurses who work for the Burn Service were selected. A survey was applied as a method for collecting information. The results are presented in absolute frequency and percentage tables. Results: The care related to skin hydration, control of electrolyte balance, stimulation of the child and his/her family, and the effects experienced by pediatric patients due to separation from the family bond are noted. Some of these effects are the rupture of roles and anguish, as well as somatization disorders and acute stress. Conclusions: There are difficulties in establishing care for pediatric patients with burns and effects due to separation from the family bond; which makes us think about strategies in favor of the performance of these professionals, and the re-establishment of pediatric patients with burns.